Unveiling narratives: representation of same-sex love in bollywood films - Prasitha V; Bhuvaneswari G (Humanities & Social Sciences Communications, 2024)
Abstract The cultural history of India has been ignorant of various sexual orientations and gender identities leaving LGBTQIA+ (Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, Asexual) community with a life of guilt and shame. Visual Media plays a key role in shaping society’s opinion of LGBTQIA+ people and individuals who come to terms with their gender and sexuality at a particular phase of their lives. The representation of homosexual characters is constantly diversified in Bollywood, and the change is evident from being caricatured and even scorned to being shown as prominent protagonists. The growing visibility and the positive portrayal of homosexual characters in Bollywood help to create a more inclusive society. This paper focuses on the select Bollywood films, Ek Ladki Ko Dekha Toh Aisa Laga (2019) by Shelly Chopra Dhar and Shubh Mangal Zyada Saavdhan (2020) by Hitesh Kewalya. The paper analyses the visual elements in select films and their role in shaping the portrayal of homosexuality within the narrative. The paper also reads the chosen films through the lens of familial resistance to same-sex relationships. By analysing the select films, the paper concludes that, though prior Bollywood films have explored the theme of individuals disclosing their sexual identity to their families, the primary narrative focus is not on seeking acceptance from their family members. Thus, the unique emphasis on seeking acceptance and understanding between family members and homosexual individuals set the select films as exceptional narratives within the context of Bollywood’s portrayal of homosexuality.